2020
DOI: 10.3390/nu12051215
|View full text |Cite
|
Sign up to set email alerts
|

Biological and Computational Studies for Dual Cholinesterases Inhibitory Effect of Zerumbone

Abstract: Acetylcholinesterase (AChE) and butyrylcholinesterase (BChE) mediate the degradation of acetylcholine (ACh), a primary neurotransmitter in the brain. Cholinergic deficiency occurs during the progression of Alzheimer’s disease (AD), resulting in widespread cognitive dysfunction and decline. We evaluated the potential effect of a natural cholinesterase inhibitor, zerumbone, using in vitro target enzyme assays, as well as in silico docking and ADMET (absorption, distribution, metabolism, excretion, and toxicity) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 27 publications
(44 reference statements)
0
11
0
Order By: Relevance
“…In this study, the effect of zerumbone was tested individually, and also in combination with EPA þ DHA, as zerumbone is a potential antioxidant molecule and may support brain cell's functional integrity by protecting the EPA þ DHA from oxidative insults under hyperlipidaemic conditions (2,25) . In addition, it has been shown that zerumbone exhibits physicochemical properties suitable for higher bio-availability and blood-brain barrier (BBB) permeability (26) . The hippocampus plays a critical role in the consolidation of information from short-term memory to long-term memory, and in spatial memory that enables navigation.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the effect of zerumbone was tested individually, and also in combination with EPA þ DHA, as zerumbone is a potential antioxidant molecule and may support brain cell's functional integrity by protecting the EPA þ DHA from oxidative insults under hyperlipidaemic conditions (2,25) . In addition, it has been shown that zerumbone exhibits physicochemical properties suitable for higher bio-availability and blood-brain barrier (BBB) permeability (26) . The hippocampus plays a critical role in the consolidation of information from short-term memory to long-term memory, and in spatial memory that enables navigation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, macrophage infiltration and pro-inflammatory cytokine production in hyperglycemia-treated kidneys were inhibited by zerumbone [21]. Furthermore, it inhibited acetylcholinesterase activity and reduced memory deficits in scopolamine-treated animal models of dementia [22,23]. Based on previous reports on the neuroprotective and anti-inflammatory effects of zerumbone, we hypothesized that zerumbone can sufficiently inhibit microglial activation and provide neuroprotection.…”
Section: Introductionmentioning
confidence: 92%
“…A wide array of molecular targets have been reported in existing literature on this the α,β-unsaturated, carbonyl-based compound, which has great potential for cancer and nociceptive treatments [ 30 , 31 ]. Recently, Hwang et al [ 32 ] reported on the pharmacokinetic properties of zerumbone, which possesses good water solubility with blood–brain barrier and central nervous system (CNS) permeability values using absorption, distribution, metabolism, excretion, toxicity (ADMET) simulation. Using in silico methods, zerumbone has shown binding capacity to several proteins and receptor sites [ 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the vast amount of literature on zerumbone’s characteristics, interactions of this compound with potassium channels and opioid receptors remain unknown. Based on docking analysis, the α,β-unsaturated carbonyl scaffold is the main force responsible for zerumbone’s therapeutic effects [ 32 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%